Professional Development Program on Innovative Teaching Methods for Beginner Science Teachers - Muhamad Taufiq; Ari Widodo; Ida Kaniawati; Liliasari Liliasari; Achmad Samsudin (Journal of Innovation in Educational and Cultural Research, 2024)
Professional Development Programs (PDPs) play a crucial role in enhancing the teaching skills of beginner science teachers, particularly in the area of Innovative Teaching Methods. This research aims to analyze the implementation of a professional development program on innovative teaching methods for beginner teachers based on their age and teaching experience. The research applies a qualitative descriptive method. The research sample consists of science teachers who attend the teacher professional program at one of the state universities in Semarang, Indonesia. Data were collected using questionnaires and tests. The research results show that higher age only sometimes indicates better teaching experience. Longer teaching experience also does not determine better mastery of skills in modifying learning methods at the end of the training. The initial mastery of teaching methods, motivation towards achieving targets, and expectations of the development program have a more significant influence on the achievement of mastery in innovative modification skills of science learning methods. This research contributes to understanding professional development programs by demonstrating that personal factors are more critical in improving beginner teachers' innovative teaching methods than age or teaching experience alone.